2004
DOI: 10.1111/j.0269-8463.2004.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of nitrogen to cell walls decreases photosynthetic nitrogen‐use efficiency

Abstract: Summary1. Nitrogen (N) is an essential limiting resource for plant growth, and its efficient use may increase fitness. We investigated photosynthetic N-use efficiency (photosynthetic capacity per unit N) in relation to N allocation to Rubisco and to cell walls in Polygonum cuspidatum Sieb. et Zucc. which germinated in May (early germinators) and August (late germinators). 2. There was a significant difference between early and late germinators in photosynthetic capacity as a function of leaf N content per unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
250
9
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(283 citation statements)
references
References 36 publications
20
250
9
4
Order By: Relevance
“…This negative relationship has been previously reported for herb, shrub and tree species (Poorter and Evans 1998). Such a dilution of photosynthetically active N as leaf increases its mass per unit area may be related to an increase in C/N ratio, as well as to a higher biomass allocation to cell walls (Onoda et al 2004). Furthermore, the negative correlation between PNUE and LMA may also explain the lower PNUE reported for leaves that have a lower leaf lifespan (Hiremath 2000).…”
Section: Species Growth and Resource Use Efficiency In Tropical Plantsupporting
confidence: 64%
“…This negative relationship has been previously reported for herb, shrub and tree species (Poorter and Evans 1998). Such a dilution of photosynthetically active N as leaf increases its mass per unit area may be related to an increase in C/N ratio, as well as to a higher biomass allocation to cell walls (Onoda et al 2004). Furthermore, the negative correlation between PNUE and LMA may also explain the lower PNUE reported for leaves that have a lower leaf lifespan (Hiremath 2000).…”
Section: Species Growth and Resource Use Efficiency In Tropical Plantsupporting
confidence: 64%
“…1). This particular difference in leaf morphology between functional types is critical since it provides contrasting nitrogen and water-use efficiencies and different leaf life spans (Terwilliger et al 2001;Onoda et al 2004). In a parallel study conducted in the same experimental site we found a positive relationship between SLA and leaf photosynthetic nitrogen use efficiency (PNUE) (Delagrange et al 2008) and Kitajima (1994) and Walters et al (1993), among others, have reported higher photosynthetic rates and SLA values for pioneer species than for non-pioneers when growing under high light conditions.…”
Section: Structural and Allocational Differences Among Tropical Treementioning
confidence: 52%
“…In this study, we did find that the LMA tended to be positively correlated with punch toughness and strength but this trend was not significant (Pearson correlation onetailed test, r = 0.032, p = 0.065 and r = 0.022, p = 0.107, respectively). Leaf cell walls constitute a substantial amount of nitrogen and account for 30-50 % of leaf dry mass, therefore a large amount of cell walls could increase leaf structural toughness which, in turn, would contribute to a greater tolerance to physical damage (Onoda et al 2004). In this study we found that the invasive J. vulgaris genotypes had a 10.8 % lower amount of cell wall proteins per leaf area than the native genotypes, which resulted in a significantly poorer structural defense to herbivory.…”
Section: Structural Defensementioning
confidence: 99%